A practical heparin reduction algorithm: execution and operational characteristics. Issue 4 (April 1985) - Branson, H E; van Stralen, D; Schottinger, J; Peters, W; Endo, Y
Abstract : A limited pilot study has been made of a newly devised heparin reduction algorithm (HRA). This formulation is a derivative of the alternative surveillance plan known as the activated partial thromboplastin time after heparin removal (aPTT/HR) scheme. Unlike the traditional plan, the HRA is the first approach to provide information about the individual and collective pharmacological effects of heparin and coumarins when the drugs are administered simultaneously. In this feasibility study the HRA was used without incident in six patients every 24 h to calculate the trend of the evolving anticoagulant effect of coumarin. The computations provided by a laboratory based data management group permitted the clinician to titrate precisely the withdrawal of heparin in response to the daily fluctuations in coumarin effect. In this way, the activated partial thromboplastin time could always be maintained within the desired therapeutic interval. Three divergent patient experiences are presented to demonstrate the operational characteristics and responsiveness of the new HRA plan.